(untitled) (The Journal of Psychology and Sociology, 2019)
The relevance of the study is dictated by the contradiction between modern requirements for professional values of the management on the one hand and the growth of national consciousness with a tendency to determine the behavior of national values on the other. The analysis of the scientific literature showed the difference of the methodological approaches to Ego-image and Ego-concept of the leader. The integrative approach allows one the self-concept as a system of expectations, attitudes, beliefs and ideas about myself, performing important functions in a person’s life, and the image of the self as a result of self-knowledge, self-attitude and self-regulation. The content of the cognitive and emotional component of the Self-image is substantiated through self-identification with its reference role group is substantiated. The disagreement between the images “Ego-real” and “Ego-ideal” leads not only to unproductive business interaction, but also to intrapersonal conflict. The description of the experimental data of specificity of professional Ego-image of men and women of heads is carried out. Comparative analysis showed a differentiation of the image data along the dimensions of “self-worth”, “self-acceptance”. “сomprisesalmost», «automate». As a problem zone, there was the discrepancy in the parameter «unrealized opportunities» in both groups of respondents was revealed, while women in this area received the most negative assessment. This shows the resource component of the potential and its focus in women leaders. Key words: Ego-image, Ego-concept, Ego-ideal, Ego-real, self-acceptance, self-attitude.